PENGARUH GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK DI CAFÉ KOPILOGI KABUPATEN GARUT - Rifki Rosyad Karnawan (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2022)
This study aims to determine the effect of lifestyle on product purchasing decisions at Kopilogy Café in Garut Regency in Leles District. The method used is to describe the results of the research using the causal method. The population is the people in Leles District. The technique used is to determine the special characteristics of the respondents. The characteristics are that the people of Leles District have bought products at Café Kopilogy. The tool used to analyze the data is SPSS. The data collection technique used was to distribute questionnaires to the people of Leles District who had visited Café Kopilogy, Garut Regency. It can be seen that the Lifestyle variable is considered good by the respondents. Lifestyle is a benchmark for someone in Purchasing Decisions because all actions taken by consumers are based on Activities, Opinions and Interests, even though there are low ratings from respondents in terms of Products at Café Kopilogy, but overall Lifestyle can influence Purchase Decisions with that seems to have gotten enough attention from respondents who are Leles District Communities. Based on the results and analysis of data and discussion, it can be seen that there is an effect of lifestyle on product purchasing decisions at Café Kopilogy, Garut Regency.